Acute gastroenteritis due to food poisoning in public spaces: A dissertation review (International Seven Journal of Health Research, 2024)
Foodborne gastroenteritis is an inflammatory process of the digestive tract caused by ingesting water and food contaminated with microorganisms, commonly bacteria and viruses. The survey aimed to find out about the possible causes of food poisoning in the popular diet and its prophylaxis, considering the high prevalence in low-income populations, as well as the natural history, environmental risk factors and measures to prevent food poisoning. This exploratory study analyzed a documental study of ten scientific articles, selected using the terms: Food poisoning, gastroenteritis, microorganism, food hygiene, written in Portuguese, English and Spanish, available online on the Scientific Electronic Library Online (SciELO), Web of Science and National Library of Medicine (PubMed/Medline) platforms, Virtual Health Library (VHL) and Google Scholar, between 2017 and 2024. Infectious diarrhea is among the leading causes of illness worldwide, with a prevalence of 1.5 to 2.5 million deaths per year. Bacteria, viruses and other parasites are the causes of acute gastroenteritis, with food-borne viruses such as norovirus, rotavirus and adenovirus standing out. Norovirus is the main non-bacterial cause globally. Serious bacteria include non-typhoidal Salmonella and Campylobacter, especially in developed countries such as the United States and New Zealand, while in Brazil, where basic sanitation is precarious in certain areas, Salmonella and E. coli are more prevalent. Worldwide, 600 million people fall ill every year from water- and food-borne diseases, resulting in 420,000 deaths. In Brazil, from 2007 to 2020, there were an average of 662 outbreaks a year, with 156,691 patients, 22,205 hospitalizations and 152 deaths. More than 60% of cases of food-borne illnesses are the result of careless hygiene by food handlers, inadequate food processing techniques and poor hygiene in the physical structure, utensils and equipment. The implementation of good hygiene practices is fundamental in guaranteeing the safety of the food offered in popular restaurants. These measures and procedures aim to prevent food contamination and ensure the hygienic quality of the products, from their origin to their final consumption. It can therefore be concluded that food poisoning is a serious public health problem, especially in terms of the high risk of infection it poses to people who eat in public spaces.